Interpreting Communist Systems and Their Differences in Operation and Transformation as Networks - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
Why some party-states collapse and others don't? Why some transformations are accompanied by economic crisis while others by economic growth? Are first political or economic transformation strategic alternatives? This paper comprises the essence of the authors comparative research on party-state systems in Europe and Asia embodied in a comparative interactive party-state model interpreted as network. Networks evolve during the decision-making process formed by the tightly intertwined dependency and interest promotion relationships among actors in the party, the state, and the economy. The model also describes the structural background of the different operation and transformation of party-state systems as specific patterns of power distribution in the network forging the different ways and instruments of self-reproduction, and different sequence, speed and conditions of system transformation.
Keywords: P2; P5; D78; F5; P21; P26; P30; 330; party-state systems; network; varieties of power distribution; selective resource distribution; political rationality of economic behavior; transformation; China